Brazed Carbon Nanotube Arrays: Decoupling Thermal Conductance and Mechanical Rigidity. Issue 5 (27th January 2017) - Hao, Menglong; Kumar, Anurag; Hodson, Stephen L.; Zemlyanov, Dmitry; He, Pingge; Fisher, Timothy S.
Abstract : Bonding two solids at their interface is the most effective way to achieve a mechanically robust and thermally conducting interface. However, for high‐temperature applications, bonded interfaces between dissimilar materials experience high thermomechanical stress that degrades their performance in terms of cyclic stability (under thermal load) and lifetime. The present study shows that integrating a carbon nanotube (CNT) array as a stress‐relief element to a traditional braze joint mitigates the adverse effects of thermomechanical stress while preserving mechanical robustness and excellent heat transfer characteristic at the interface. A substantial reduction in total thermal interface resistance is achieved (from 41 mm 2 K W −1 for bare CNT array to less than 3 mm 2 K W −1 for a CNT array integrated with braze alloy). A brazed metal/insulator interface (between Cu and quartz) with a CNT array between them exhibits low thermal interface resistance even after extreme thermal cycling whereas the same interface delaminates readily when brazed without a CNT array. The reported technique provides a promising route for substantially improving the problematic high‐temperature interface, a major hindrance in achieving stable and efficient operation for systems such as thermoelectric generators that operate at elevated temperatures (above 400 °C). Abstract : A method of brazing vertically oriented carbon nanotube (CNT) arrays for thermal interface applications is presented. Carbide formation occurs at heterogeneous material interfaces, and high thermal interface conductances are measured. Because of the mechanical compliance of CNT arrays, this interface material survives extreme thermal cycling and thermal shock, sustaining its thermal and mechanical integrity, despite experiencing enormous thermal strain.